Food irradiation: Comparative, historical and diffusion review of the process - Ramos, Ricardo; Batista, Eutropio Vieira (Brazilian Journal of Science, 2023)
The use of irradiation in food is not a new technique, but it has shown relevant advances in its acceptance and in the benefits that it can provide to food. Therefore, this work aimed to evaluate the history of the use of the irradiation technique in food. As well as observe what were the main benefits and methodologies employed. Then, it was found that this is a safe and efficient technique to increase the shelf life of foods and get rid of pathogens. In addition, it presents a very important regulation that guarantees quality and safety for these foods, further spreading the process in the social and academic environment.